Southern Africa Pandemic Management in Sports: Observations from the 1918 Influenza and COVID-19 - Terence Tapiwa Muzorewa; Aaron Rwodzi (2023)
This chapter evaluates pandemic management systems adopted by southern African sporting communities in responses to the 1918 ‘Spanish’ Influenza and the novel Corona virus pandemic. The two pandemics which occurred in two different historical epochs disturbed sporting activities world-wide, upset social relations, triggered community anxieties, and resulted in shutdown of all sporting activities. This study serves as a litmus test of the current sporting communities in southern Africa to adopt, in unison, effective and timely disaster response mechanisms in order to save human lives from devastating natural phenomena while guaranteeing livelihoods of sports women/men. The chapter argues that sporting policy interventions and institutional frameworks adopted in an endeavour to curb the spread of the pandemic were either weak or ineffective. The argument is based on an analysis of the various dynamics which shaped the pandemic management systems such as racism, class and ad hoc policy (in)consistencies by sporting governments in line with World Health Organisation (WHO) prescriptions. The chapter also has the novelty of exposing the challenges that the poor sporting communities in southern Africa have in procuring resources to survive pandemics. Because Covid-19 is a contemporary phenomenon, the methodological approach is underpinned by a qualitative analysis of data collected through desktop research, government primary documents, virtual interviews and webinar discussions. Both secondary and primary sources are used to derive data on the 1918 Influenza. After a comparative analysis of the two pandemics, the chapter argues that although the pandemics occurred during two astronomically different periods, there have not been many significant changes in pandemic management systems.